ANALYSIS OF AIR TRAFFIC MANAGEMENT IN SOME MAJOR AIRPORTS OF THE WORLD - N. A. Assorov (Научный вестник МГТУ ГА)
The article analyses advantages and disadvantages in air traffic management and flow management in airports of London, Paris and Frankfurt. Some positive experience in ATM that can be used in Moscow airspace is described.